Recent advances in neuroimaging of Alzheimer's disease and related dementias - Ottoy, Julie; Owsicki, Nicole; Bilgel, Murat; Binette, Alexa Pichet; Salvadó, Gemma; Kang, Min Su; Cash, David M.; Ewers, Michael; La Joie, Renaud; Wisse, Laura E.M. ; 0000-0001-7504-3943; Goubran, Maged; Betthauser, Tobey (Alzheimer's and Dementia, 2025)
This review covers recent advances (2023–2024) in neuroimaging research into the pathophysiology, progression, and treatment of Alzheimer's disease (AD) and related dementias (ADRD). Despite the rapid emergence of blood-based biomarkers, neuroimaging continues to be a vital area of research in ADRD. Here, we discuss neuroimaging as a powerful tool to topographically visualize and quantify amyloid, tau, neurodegeneration, inflammation, and vascular disease in the brain. We examine the utility of neuroimaging for (1) tracking the spatiotemporal progression of pathology, (2) serving as the reference standard for validating novel fluid biomarkers, (3) characterizing disease heterogeneity, (4) exploring the role of brain networks in ADRD progression, and (5) evaluating biomarkers for better individualized estimates of treatment benefit. Finally, we discuss advances in radiotracer development and AD risk factors. By reviewing the most promising breakthroughs in the neuroimaging field, we hope to spark new ideas for future discoveries that will deepen our understanding of ADRD. Highlights: The diagnostic and staging criteria for Alzheimer's disease (AD) were updated in 2024. Despite robust harmonization methods for amyloid beta positron emission tomography (PET), parallel efforts for tau PET remain challenging. Larger anti-amyloid drug effects were seen at lower levels of amyloid and tau PET. Phosphorylated tau217 (p-tau217) is currently the most promising plasma biomarker to detect AD pathology. There are new tracer developments for alpha-synuclein, primary tauopathies, and inflammation.
Keywords: Alzheimer's disease; amyloid; cerebrospinal fluid biomarker; cerebrovascular disease; clinical trials; co-pathology; connectivity; disease staging and subtyping; heterogeneity; inflammation; neuroimaging; plasma biomarker; positron emission tomography; risk factors; tau